Edukasi Pencegahan Hipertensi pada Ibu Hamil di RW 01 Desa Babakan - Meti Kusmiati; Abdya Andini; Ade Fitriyani; Amanda Adisti; Cecilia Zonaffel (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Based on initial observations in the field, pregnant women lacked awareness of participating in posyandu activities due to lack of knowledge and the location being considered too far. The benefit of preventing hypertension for society is that it can reduce the maternal mortality rate (MMR) and infant mortality rate (IMR). The aim of this education is to increase mothers' knowledge about preventing hypertension and reducing complications that occur in pregnant women. The activity method is carried out through counseling, providing direct material using media, posters and booklets as well as pre-tests and post-tests to measure knowledge about preventing hypertension in pregnant women. The results of this community service activity showed that there was a significant influence on increasing the knowledge of mothers with toddlers about the importance of posyandu for monitoring growth and development as evidenced by the pretest scores which showed that the number of people who had poor knowledge was 18 people (72.0%), and the results The post test showed that the number of people who had good knowledge was 7 people (28.0%). In conclusion, there is an impact on increasing pregnant women's knowledge about preventing hypertension preganant.